Konstruksi Integratif Keilmuan Islam, Akhlak, dan Kemandirian Santri dalam Pendidikan Pesantren: Studi Kasus di Pondok Pesantren Darul Falah Rakit Banjarnegara - Nasywa, Syaif Khulaidatun; Hanifah, Salma Hanan; Tarikul Majid, Ahmad (DAS Institute, 2025)
This study is motivated by the tendency of studies on pesantren education to discuss Islamic scholarship, moral development, and students’ independence separately. In practice, however, these three aspects are interconnected and form an integrated educational process within pesantren education. This study aims to analyze the integrative construction of Islamic scholarship, morality, and students’ independence in the educational process at Pondok Pesantren Darul Falah Rakit Banjarnegara. This research employs a qualitative approach using a case study design. Data were obtained through observation, in-depth interviews with the pesantren leader, ustaz, administrators, and students, as well as documentation of pesantren activities and regulations. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, using source and technique triangulation. The findings show that Islamic scholarship serves as the foundation for shaping students’ ways of thinking and values; morality is developed through role modeling, habituation, and supervision; while independence is formed through dormitory life and daily responsibilities. These three elements are integrated within the pesantren culture, which unites learning, guidance, and students’ lived experiences. The theoretical contribution of this study lies in strengthening the concept of pesantren education as a holistic-integrative educational model, namely education that emphasizes not only mastery of religious knowledge but also the formation of manners, responsibility, and life independence among students.